Mengajarkan Kasih Kristiani di Tengah Keberagaman Budaya dan Agama - Hepni Putri; Presi Nila Sari; Semuel Linggi Topayung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the importance of teaching Christian love amid the cultural and religious diversity in Indonesia. Diversity, which is a national treasure, should be nurtured through inclusive humanitarian values, where every individual is viewed as a fellow being worthy of love and respect. In this context, Jesus' teachings about love for one another and Martin Buber's concept of